Fishing with traps and pots - R. J. SLACK-SMITH (FAO, 2001)
This manual describes the elements of fishing with traps and pots for small-scall fishermen. It presents the various types of traps and pots and their construction and gives guidance on how to choose the appropriate gear, how to rig it, how to use it to improve the catch, how to selcte places to fish, soaking time and finally care of the catch.